ONLINE COURSE OF SUSTAINABLE DEVELOPMENT GOALS: AN EXPERIENCE REPORT - Marquetto, Bruno de Andrade; Villegas, Valéria Carolina Armas; Linhares, Rebeca Coêlho; da Silva, Guilherme Araújo; Santana, Clara Marques; Vasconcelos, Any Carolina Cardoso Guimarães (Brazilian Medical Students, 2021)
INTRODUCTION: The Sustainable Development Goals (SDGs) were defined by the United Nations in the preparation of the 2030 Agenda and represent an attempt at a global effort to poverty eradication, environmental protection, sustainable development and the establishment of decent living conditions. In this context, the link between health and sustainable development stands out, especially when we bring planetary health, significant youth engagement and global health to the fore, it expands health promotion within the reach of all the SDGs. EXPERIENCE REPORT: The I Course on Sustainable Development Goals of International Federation of Medical Students Associations of Brazil (IFMSA Brazil) was developed between October 8 and 10 with the objective of promoting the debate on the SDGs in an integrated manner with the IFMSA Brazil's main discussion themes. The event was restricted to 40 participants for better theoretical-practical interaction and held by the Zoom platform. DISCUSSION: Considering the alarming finding of only 20.5% of the participants with any previous contact with SDGs in the curriculum, the discussion of this topic is very important. This fact is emphasized with the current scenario in Brazil, as recent research shows that the country will hardly reach the Agenda's goals, especially with regard to health, which is the scope of the target audience of the course. Social accountability promoted by medical schools is an important way of promoting SDGs by medical students. CONCLUSION: The event forms showed that the event fulfilled its purpose of presenting the SDGs to the participants and integrating them with practical ideas about its approach, thus enabling these students to promote changes in their local realities with the community.